Complexation of Polyelectrolytes with Hydrophobic Drug Molecules in Salt-Free Solution: Theory and Simulations - Lei, Qun-li (2017)
The delivery and dissolution of poorly soluble drugs is challenging in the pharmaceutical industry. One way to significantly improve the delivery efficiency is to incorporate these hydrophobic small molecules into a colloidal polyelectrolyes(PE)–drug complex in their ionized states. Despite its huge application value, the general mechanism of PE collapse and complex formation in this system has not been well understood. In this work, by combining a mean-field theory with extensive molecular simulations, we unveil the phase behaviors of the system under dilute and salt-free conditions. We find that the complexation is a first-order-like phase transition triggered by the hydrophobic attraction between the drug molecules. Importantly, the valence ratio between the drug molecule and PE monomer plays a crucial role in determining the stability and morphology of the complex. Moreover, the sign of the zeta potential and the net charge of the complex are found to be inverted as the hydrophobicity of the drug molecules increases. Both theory and simulation indicate that the complexation point and complex morphology and the electrostatic properties of the complex have a weak dependence on chain length. Finally, the dynamics aspect of PE–drug complexation is also explored, and it is found that the complex can be trapped into a nonequilibrium glasslike state when the hydropobicity of the drug molecule is too strong. Our work gives a clear physical picture behind the PE–drug complexation phenomenon and provides guidelines to fabricate the colloidal PE–drug complex with the desired physical characteristics.